Modified Newtonian Dynamics: A Falsification of Cold Dark Matter - R. H. Sanders (Advances in Astronomy)
The only viable alternative to dark matter is one in which Newtonian dynamics or gravity breaks down in the limit of low accelerations, as in modified Newtonian dynamics (MONDs). This hypothesis, suggested by Milgrom, has been successful in explaining systematic properties of spiral and elliptical galaxies and predicting in detail the observed rotation curves of spiral galaxies with only one additional parameter—a critical acceleration which is on the order of the cosmologically interesting value of 𝑐𝐻𝑜. MOND may be viewed as an algorithm for calculating the distribution of force in an astronomical object from the observed distribution of baryonic matter. The fact that it works very well on the scale of galaxies is problematic for cold dark matter (CDM). Here I present evidence in favor of this assertion and claim that this is, in effect, a falsification of CDM on the scale of galaxies.